Densification of AlON ceramics doped with Y2O3-La2O3-MnO additives at lower sintering temperature. Issue 4 (March 2019) - Guo, Huilu; Mao, Xiaojian; Zhang, Jian; Tian, Run; Wang, Shiwei
Abstract: Attempts have been made to manufacture AlON transparent ceramics at low temperature using a new sintering aid system, Y2 O3 -La2 O3 -MnO. The sintering behaviors, including relative density and microstructure evolution of AlON ceramics doped with Y2 O3 -La2 O3, MnO alone, and Y2 O3 -La2 O3 -MnO were compared. It was found that both the relative densities and grain sizes of samples doped with Y2 O3 -La2 O3 -MnO were much higher and larger than those of samples doped with Y2 O3 -La2 O3 or MnO alone, respectively. A liquid phase containing Al, O, N, Mn, and La formed at high temperature and played an important role on both eliminating pores and promoting grain growth of the sintered AlON bodies. Finally, translucent AlON ceramics were obtained through pressureless sintering at 1830 °C for 1 h, ~100 °C lower than those with conventional sintering aid Y2 O3 -La2 O3 . The ceramics doped with MnO showed green emission at 534 nm, under 445 nm excitation. We believe Y2 O3 -La2 O3 -MnO is a promising additive for the preparation of AlON transparent ceramic at lower temperature.